(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2015)
Introduction: Assessing the health related quality of life (HQoL) and depression in human immunodeficiency virus (HIV) positive people and TB-HIV co infected people is of extreme importance in designing strategies and implementing interventional programs on treatment care and support to People living with HIV and AIDS. Methodology: A cross-sectional study was conducted among People living with HIV/AIDS and TB-HIV Co infection from July to December 2011 at care and support canters in Kathmandu, Nepal. The list HIV care and Support centre registered at Kathmandu were selected using the lottery proportionately to meet the sample size of 154. The method of data collection was summarized in the World Health Organization’s questionnaire for Health related Quality of life and Beck Depression Inventory Scale II for depression. Data was collected using verbal information of respondents, entered on Epi Data version3.4.1 and analyzed using SPSS version 16.0. Results: TB-HIV co infected people had lower quality of life in all domains compared to HIV/AIDS infected people. The prevalence of depression was found higher in TB-HIV co infected people than HIV/AIDS group. CD4 count, educational status, occupation, ethnicity, family size and depression were statistically significant with the QoL domains. Among co infected patients, depression was 3.86 times more likely to influence QoL while adjusted odds ratio was 4.21 times higher. Conclusion: The TB control program should design strategies to improve the quality of life of TB-HIV co infected people and depression should be targeted as an intervention to improve the quality of life of people living with HIV with or without TB. DOI: http://dx.doi.org/10.3126/saarctb.v11i2.12428 SAARC J TUBER LUNG DIS HIV/AIDS, 2014;XI(2) Page: 7-14